SARS-CoV-2 Transmission and Epidemic Characteristics in Jining City, China - Jianwei Zhou; Yu Li; Cui Kong; Jiang Yu; Yizhao Li; Qinghua Zhang; Yao Liang (Faculty of Medicine Universitas Padjadjaran, 2021)
Background: Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) that causes severe acute respiratory syndrome has spread to hundreds of countries and infected millions of people, causing more than a hundred thousand deaths. This study aimed to describe the epidemic characteristics of SARS-CoV-2 and its transmission in a city in China.Methods: This was a descriptive study on retrospective data collected from January to February 2020 from reports issued by the authority of Jining City, China, including data on travel history, transmission, gender, and age of infected persons. Results: During the period January and February 2020, 52 cases were confirmed to be SARS-CoV-2 infections with more than half were males (n=32, 61.5%) and and in the age grup of 31–50 yars old (53.8%). The modes of transmission were mostly primary infections (n=23) and a history of travel to and from outside of Shandong Province (n=14). Interestingly, the infection was the 4th transmission and most primary infectious persons did not transmit the virus to others.Conclusions: The key characters of infected people in Jining City in early epidemic time with the exception of exogenous inputs are male gender, city dweller, and middle-aged people of 31–50 years old. There is a restricted transmission in Jining City of China at the early phrase of the SARS-CoV-2 epidemic, indicating that the strategy for the fight against SARS-CoV-2 is effective to some extent and worth to be learned by the members of the global village. This strategy includes actions such as home isolation, collective centralized quarantine, social distancing, and face mask use.